2021
DOI: 10.1186/s13005-021-00265-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen deficiency during puberty on maxillary and mandibular growth and associated gene expression – an μCT study on rats

Abstract: Background Estrogen is a well-known and important hormone involved in skeletal homeostasis, which regulates genes involved in bone biology. Some studies support that estrogen is important for craniofacial growth and development. Therefore this in vivo animal study aimed to investigate, whether and in which way low estrogen levels in the prepubertal period affect craniofacial development in the postpubertal stage and to quantify the gene expression of RANK, RANKL and OPG in cranial growth sites … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…80% to 90% of serum levels of vitamin D are synthesized endogenously under UVB irradiation, the remainder, 10% to 20%, come from the diet, the main dietary sources being cholecalciferol (D 3 ) and ergosterol (D 2 ). Estrogen deficiency and vitamin D deficiency share several adverse health outcomes, including bone resorption itself, mood disorders, increased risk of cardiovascular disease and cancers [24][25][26][27][28] affect growth and development [2][3][4][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…80% to 90% of serum levels of vitamin D are synthesized endogenously under UVB irradiation, the remainder, 10% to 20%, come from the diet, the main dietary sources being cholecalciferol (D 3 ) and ergosterol (D 2 ). Estrogen deficiency and vitamin D deficiency share several adverse health outcomes, including bone resorption itself, mood disorders, increased risk of cardiovascular disease and cancers [24][25][26][27][28] affect growth and development [2][3][4][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of estrogen could cause various problems during different periods of women’s lifetime. Experimental evidence has confirmed that estrogen deficiency during the prepubertal period affects craniofacial growth and development [ 25 ]. Some researchers considered that the absence of estrogen may cause obesity among menopausal women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…High estradiol concentrations in late adolescence led to growth plate closure ( Börjesson et al, 2012 ). In prepubertal ovariectomy mice, E2 deficiency can promote both maxilla and mandible growth, accompanied by an increase in RANKL/OPG ratio ( Omori et al, 2020 ; Küchler et al, 2021 ). The loss of E2 during sexual maturity leads to reduced medullary bone formation ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a reported study on Japanese quails, E2-induced osteoclastogenesis can be regulated in the bone marrow cells via the RANK/RANKL/OPG (RANK/RANK Ligand/Osteoprotegerin) system during medullary bone formation ( Hiyama et al, 2019 ). Moreover, in prepubertal ovariectomy mice, E2 deficiency can promote both maxilla and mandible growth, accompanied by an increase in RANKL/OPG ratio ( Omori et al, 2020 ; Küchler et al, 2021 ). A low bone turnover in 20-day-old rats treated with E2 for 14 d was due to decreased bone remodeling ( Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%